Implementation of the Plavon Program in Population Administration Services - Anam , M. Syaiful; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2025)
Background: The increasing reliance on technology in public service delivery has led local governments to adopt e-government systems. Specific Background: This study explores the implementation of the PLAVON e-government program in a rural context, addressing the operationalization of such systems in local governance. Knowledge Gap: Existing research highlights e-government frameworks, yet the challenges and successes of community-level implementation remain underexplored. Aims: This research aims to analyze PLAVON's implementation, focusing on standard operating procedures (SOPs) and community engagement. Results: Findings reveal that structured SOPs enhance efficiency and transparency in public services, enabling self-service for citizens. Novelty: This study offers insights into the challenges and strategies of rural e-government implementation. Implications: Results underscore the importance of tailored bureaucratic practices and community involvement, providing valuable lessons for similar programs in rural areas. Highlights : Efficiency: Structured SOPs enhance the efficiency of public service delivery. Transparency: Clear procedures foster transparency in administrative processes. Community Involvement: Active participation of local citizens is crucial for successful implementation. Keywords: E-Government, PLAVON, SOP, Community Engagement, Rural Implementation